OXYGEN EXERCISES AND THEIR IMPACT ON THE LEVEL OF IMMUNOGLOBIN AND SOME FUNCTIONAL INDICATORS AND PERFORMANCE TOLERANCE OF WRESTLERS - Ahmed Razzaq Zghair; Prof. Dr. Ammar Jasim Muslm (Scholars Digest Publishing, 2024)
The exercise of sports activities, especially the organization, aims to develop the special physiological abilities required to perform the sporting activity of the individual. The exercise of these activities undoubtedly leads to numerous adaptations in the functional organs of the body. These biological adaptations that occur in the internal organs of the individual's body increase their functional abilities. Hence the importance of our study dealing with some of the chemical functional indicators (heart rate, respiratory rate, systolic blood pressure, diastolic blood pressure, IgG,), performance tolerance and the extent to which they are affected by oxygen exercises. The research problem is identified in the statement of the role of oxygen exercises on the heart, blood vessels, immune proteins "globes" and performance tolerance in individuals of the research sample. The research aims to prepare proposed oxygen exercises for advanced wrestlers. The two researchers drew on the pilot curriculum on a sample of 6 applicant-class wrestling players representing Basra Oil Sports Club for the season (2022 - 2023) in Basra Governorate. Physical effort was represented by performance tolerance testing. Through the results of the research, the most important conclusions emerged. 1- The exercises prepared by the two researchers have had a positive impact on the chemical functional indicators and the performance tolerance of the wrestlers applying to the Basra Oil Sports Club. 2- Oxygen exercises have advanced both the functions of the heart muscle and the periodic and respiratory system
Keywords: oxygenic exercises: globin: circulatory and respiratory system.